Comparison of trophic spectrum in the blackspot seabream, Pagellus bogaraveo (Brünnich, 1768), between cold-water coral habitats and muddy bottoms in the central Mediterranean. (March 2021) - Capezzuto, Francesca; Ancona, Francesco; Calculli, Crescenza; Carlucci, Roberto; Sion, Letizia; Maiorano, Porzia; D'Onghia, Gianfranco
Abstract: The present study represents the first documentation of the trophic spectrum of the deep-water bony fish Pagellus bogaraveo in two different habitats in the central Mediterranean Sea: muddy bottoms (MB) and cold-water coral (CWC) habitats. A total of 133 stomachs were collected on MB and 39 in CWC habitats. The feeding habit of P. bogaraveo was different in the two investigated habitats. A lower number of prey categories were found in CWC habitats (15) than on MB (36). Teleostei (%PSIRI = 38.29) and Crustacea (%PSIRI = 36.49) were the most important prey in MB. The taxon of Anellida was the most abundant in number and the third in importance. In CWC habitats Teleostei were the most abundant prey (%PSIRI = 62.03) and Ophiuroidea were the second important ones. Ontogenetic dietary variation was evident in both habitats. The comparison of the diet between the habitats was carried out considering two samples of specimens with overlapping sizes, 21 on MB and 18 in CWC habitats, ranging between 192 and 280 mm total length (TL) from the former habitat and 184 and 271 mm TL from the latter. Dietary differences were significant as shown both by Morisita's index and PERMANOVA. The habitat in which the species lives would seem to affect the trophic strategies of P. bogaraveo . The trophic niche breadth examined for comparable sized samples showed how P. bogaraveo was more generalist on MB (Bi = 0.406) and a little bit more specialist in CWC habitats (Bi = 0.301). P. bogaraveo resulted to occupy a higher position in the trophic web of the CWC habitats compared to that on MB. Highlights: Diet of P. bogaraveo in the central Mediterranean. Comparison of the diet P. bogaraveo between muddy bottoms and CWC habitats. Teleosts and crustaceans dominated in the diet on the muddy bottoms while teleosts in CWC habitats. The trophic level was higher in CWC habitats than on the muddy bottoms. A habitat effect is observed on the diet of P. bogaraveo .